Analisis Berpikir Kritis Siswa SMP dalam Memecahkan Masalah Numerasi Ditinjau dari Persepsi Diri terhadap Kompetensi Matematika - Kusumawati Indriansyah, Riandita; Firdaus, Hana Puspita Eka; Galatea, Chusnul Khotimah (Jurnal Pendidikan Matematika : Judika Education, 2025)
This study aims to analyze students' critical thinking skills in the context of numeracy in terms of their self-perception of mathematical competence. A qualitative approach was used with a case study design, involving four eighth-grade students at a junior high school in Bondowoso who were selected based on the categories of positive, negative, declining, and improving self-perception. The research instruments consisted of a self-perception questionnaire and numeracy questions analyzed using six indicators of critical thinking, namely interpretation, analysis, inference, evaluation, explanation, and self-regulation. Data were obtained through test results and interview transcripts. The results showed that students with positive and increasing self-perceptions were able to meet all six critical thinking indicators, while students with negative self-perceptions met two critical thinking indicators and students with declining self-perceptions met four critical thinking indicators. These findings indicate that positive self-perception tends to contribute to better critical thinking skills, but it was found that students with initially positive self-perception did not necessarily have high critical thinking skills. Thus, the dynamics of self-perception are an important factor that needs to be considered in the development of numeracy-based mathematics learning.   Keywords: Critical Thinking, Self-Perception, Numeracy